2021
DOI: 10.1177/09075682211055605
|View full text |Cite
|
Sign up to set email alerts
|

Seen and not heard: Students’ uses and experiences of silence in school relationships at a secondary school

Abstract: Silence is traditionally understood as a power deficit; yet, it creates spaces in which power works unobtrusively. In this article, I report the findings of a qualitative study examining silence in school relationships. Based on nine conceptual discussions and 33 interviews with teachers and students in a secondary school in the UK, I assert that uses of silence in relationships between students and teachers revolve around two conceptions of power: a stronghold of respect and a refuge for dignity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Whilst the findings of the study are reported elsewhere (Hanna, 2021a(Hanna, , 2021b, one of the key conclusions of the research was that both young people's and teachers' uses and experiences of silence were contingent on the purposes and motivations for their use. The consequences, intentional or otherwise, silent epistemologies | 10.1163/15718182-30040003…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Whilst the findings of the study are reported elsewhere (Hanna, 2021a(Hanna, , 2021b, one of the key conclusions of the research was that both young people's and teachers' uses and experiences of silence were contingent on the purposes and motivations for their use. The consequences, intentional or otherwise, silent epistemologies | 10.1163/15718182-30040003…”
Section: Methodsmentioning
confidence: 93%
“…Nonetheless, what children's participation rights are still lacking, is a coherent, comprehensive and convincing theoretical bedrock. Whilst the findings from the study upon which this paper is based have been reported elsewhere (Hanna, 2021a(Hanna, , 2021b; this paper will present a conceptual framework for children's participation rights.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing that the inherent power asymmetry between adults and young people cannot be eliminated in most research (see Hanna, 2022), we argue for the development of more reflexive and context- and participant-sensitive approaches in research involving young people. Such sensitivities apply to both data collection and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside the search for young people’s voices in research has been the acknowledgement of the need for young people to be heard by adults (Blum-Ross, 2013; Booth and Ainscow, 2011). Issues of voice and listening are visible and influential topics in debates on research with children and young people (Hallett and Prout, 2004; Hanna, 2022; Lavee and Itzchakov, 2021; Lewis, 2010; Soto and Swadener, 2016; Spyrou, 2011, 2016). Providing space for children and young people to be heard adheres to a critical paradigm shift in youth and childhood research that criticizes a conception of young people as passive receivers of adult input and views the child as an active agent capable of constructing their own subjectivity (Soto and Swadener, 2016).…”
Section: Listening To the Voices Of Children And Young Peoplementioning
confidence: 99%
See 1 more Smart Citation